A Study of How Moral Courage and Moral Sensitivity Correlate with Safe Care in Special Care Nursing - Fateme Mohammadi; Banafsheh Tehranineshat; Afsaneh Ghasemi; Mostafa Bijani (The Scientific World Journal)
Background. Nursing is a caring profession, and nurses who have moral sensitivity and moral courage presumably can provide safe and better care for patients. This study aims at investigating how moral courage and moral sensitivity correlate with safe care in special care nursing. Methods. This study is a descriptive work of research. The participants consisted of 524 nurses who were in practice in the ICU (intensive care unit), CCU (C\coronary care unit), post-CCU (postcoronary care unit), and dialysis of four hospitals located in the south of Iran selected via census sampling. Data were collected from April to September 2020 using the moral sensitivity questionnaire (MSQ), professional moral courage questionnaire (PMCQ), and the assessment of safe nursing care questionnaire (ASNCQ). The collected data were analyzed using descriptive statistics, t-test, chi-square, multiple regression analysis, and Pearson’s correlation coefficient in SPSS v. 22. Results. The mean ± SD of the nurses’ age was 33.89 ± 6.91 years, and the mean ± SD of their work experience was 9.16 ± 4.67 years. The total mean score ± SD of the nurses’ moral sensitivity was found to be 93.41 ± 2.68, the total mean score ± SD of their moral courage was found to be 96.38 ± 3.63, and the total mean score ± SD of their safe care scores was found to be 321.80 ± 9.76. The values of Pearson’s correlation coefficients showed significant correlations between moral courage and safe care (r = 0.54, p<0.001), moral sensitivity and safe care (r = 0.59, p<0.001), and moral sensitivity and moral courage (r = 0.52, p<0.001). Conclusion. There is a positive correlation between moral sensitivity and moral courage. Both positively correlated with special care nursing. Accordingly, through effective planning, education, and giving their support, nurse administrators can promote the abovementioned ethical virtues in the nursing staff, thereby improving the quality of care.